Analysis of the longitudinal effect of home advantage in the Brazilian Football Championship - Série A - Leite, W.; Zanetti, M. C. (Baltic Journal of Health and Physical Activity, 2024)
Athletes and teams typically obtain an advantage when competing at home, a phenomenon known as home advantage (HA). This study investigates the longitudinal effect of HA in the Brazilian Football Championship (Série A) over 21 seasons, analyzing 8,405 matches from 2003 to 2023. The results showed that the average HA was 35.1 ± 7.7%, while the competitive balance (CB) was 0.838 ± 0.145. A negative, non-significant correlation (r = -0.321, p = 0.157) was found between HA and CB, with CB explaining 10.3% of HA variation in the Brazilian league. HA de-creased over time, likely due to improved logistics, fairer refereeing, among others. Conversely, a gradual increase in CB was observed, evidencing a greater competitive imbalance among teams. Surprisingly, the absence of spectators during the 2020 season, due to COVID-19 restrictions, did not significantly impact HA, suggesting other influencing factors. The findings align with global trends, showing a declining HA in football leagues worldwide. This study highlights the complexity of HA, emphasizing the need for future research to explore its multi-factorial nature in Brazilian football.